Walt Whitman - American Writers 9 : University of Minnesota Pamphlets on American Writers - Chase, Richard (Book collections on Project MUSE., 1961)
Walt Whitman - American Writers 9 was first published in 1961. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.